Inelastic Response of Fixed and Flexible Foundation of Structure Under Seismic Excitations Generated Deterministically - Pranowo; Pawirodikromo, Widodo; Makrup, Lalu; Muntafi, Yunalia (Salehan Institute of Higher Education, 2025)
Researchers performed inelastic dynamic analysis on simulated ground motion while accounting for foundation flexibility in the specific area of Yogyakarta. The closest fault source to the building site is the Opak Fault, situated 2.1 kilometers from the structure. The closeness to the fault source, which suggests an exceedingly high earthquake magnitude, prompted the use of deterministic analysis. Deterministic analysis used five Ground Motion Prediction Equations (GMPEs): Campbell-Bozorgnia (2006), Sadigh et al. (1997), Ciao-Youngs (2008), Zhao et al. (2006), and Kanno et al. (2006), while the flexibility of the foundation was evaluated using the formula proposed by Novak (1989). The analysis results show that the vibration period that occurs on the flexible support is 2.8 seconds, while on the fixed support it is 2.4 seconds. Deflections and drift ratios in structures with fixed support and high-frequency content are greater, but in beam curvature the results show the opposite, namely, low-frequency content produces larger curvature values. The damage index on the fixed support and high-frequency content is greater than the others. Not much research has looked into the results of inelastic response analysis that includes hysteretic loop outputs and damage indices, making this a new area of study.